Additional file 4 of Location of studies and evidence of effects of herbivory on Arctic vegetation: a systematic map - E. M. Soininen (11566553); I. C. Barrio (11566556); R. Bjørkås (11566559); K. Björnsdóttir (11566562); D. Ehrich (11566565); K. A. Hopping (11566568); E. Kaarlejärvi (11566571); A. L. Kolstad (11566574); S. Abdulmanova (11566577); R. G. Björk (11566580); C. G. Bueno (11566583); I. Eischeid (11566586); et al. (2021)
Additional file 4. Coding template and description of coded variables. Coding template used for data entry, including descriptions of coded variables, definitions of dropdown menus and references to the spatial data sources for variables extracted from other data sources.